Non-Invasive Blood Glucose Measurements Using TCRT5000 IR Sensor - Dr. Rajalaxmi S; Ms. Abinaya K; Mr. Akilesh S; Mr. Anbirkkiniyan M S; Ms. Asha C T (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This project investigates the development of a non-invasive blood glucose monitoring system utilizing the TCRT5000 infrared (IR) sensor module. Traditional blood glucose measurement techniques rely on invasive methods that require blood samples, causing discomfort and increasing the risk of infection. To address these issues, this system aims to estimate blood glucose levels by analysing the infrared light absorption properties of blood through the skin. The TCRT5000 module, comprising an IR emitter and a phototransistor, is employed to project infrared light into the fingertip and measure the intensity of the reflected light. Variations in blood glucose levels alter the optical characteristics of blood, thereby affecting the absorption and reflection of infrared light. By calibrating the sensor outputs with readings from a standard glucometer, a correlation model is created to estimate glucose concentrations. The system is connected to a microcontroller for data acquisition, processing, and display. Though still in the prototype stage, this approach shows promise for creating a cost-effective, portable, and painless method for continuous glucose monitoring, especially suitable for diabetic patients. Further research is required to enhance accuracy and compensate for factors such as skin thickness, ambient light, and tissue composition.